KELAYAKAN TEORETIS MEDIA PEMBELAJARAN PUZZLE DIGITAL PADA MATERI STRUKTUR DNA UNTUK KELAS XII - YUSLIAWAN, KHARISMA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
The structure DNA is one of the biological topic that is abstract, so that the delivery of topic required learning media. One of the learning media that can be used is digital puzzle media. Digital puzzle media is the development of puzzle media. The development of digital puzzle aims to produce a learning media for structure of DNA topic and described its theoretical feasibility. This research is development research by ASSURE method. Research instrument used is the digital media puzzle validation sheets. The data was analyzed by quantitative descriptive. The result showed that developed media was very feasible with percentage 93.75%. Keywords: digital puzzle, DNA structure, theoritical feasibility.